The Village Development in Village Autonomy Context Based on CommunityEmpowerment (The implementation of Act Number 6 of 2014 concerning Villages) - Sri Pujiningsih (Syariah: Jurnal Hukum dan Pemikiran, 2019)
Abstract : The village development carried out in the village cannot be separated from the village autonomy authority that it has. The purpose of village development is directed at improving the welfare of the village community, supported by more and more village affairs now as stipulated in Act Number 6 of 2014. Village development cannot be carried out by one party alone, without involving other parties, therefore it must be coordinated with other parties both with the government and the community. In community empowerment it means that there is a process that builds the community through developing community capacity, changing human behavior and even reaching the level of community organizers. Village development in the context of village autonomy based on community empowerment does not always lead to the form of programs that are physical in nature. Through this writing, village development is more directed at the form of community empowerment programs.Keywords : village development, village autonomy, community empowerment  Abstrak : Pembangunan desa yang dilaksanakan di desa tidak terlepas dari kewenangan otonomi desa yang dimilikinya. Tujuan pembangunan desa diarahkan untuk peningkatan kesejahteraan masyarakat desanya, didukung pula urusan desa sekarang ini semakin banyak sebagaimana diatur dalam UU Nomor.6 Tahun 2014. Pembangunan desa tidak mungkin bisa dilaksanakan oleh satu pihak saja, tanpa melibatkan pihak lainnya, oleh karena itu harus melalui koordinasi dengan  pihak lain baik dengan pemerintah maupun masyarakat. Dalam pemberdayaan masyarakat berarti ada suatu prosesyang membangunmasyarakatmelaluipengembangankemampuan masyarakat, perubahan perilaku manusia dan bahkan bisa  sampai pada tingkatan pengorganisasi masyarakat. Pembangunan desa dalam konteks otonomi desa yang berbasis pada pemberdayaan masyarakat ini tidak selalu mengarah pada bentuk program pembangunan yang sifatnya fisik. Melalui tulisan ini pembangunan desa lebih diarahkan pada  bentuk program-program pemberdayaan masyarakat.Kata Kunci : pembangunan desa, otonomi desa, pemberdayaan masyarakat